Consent in the practice of molecular HIV epidemiology: A qualitative study of the perspectives of diverse communities of interest - S. Rennie; U. Onyeama; K. Sullivan; S. Day; A. Dennis (PLoS ONE, 2025)
Background The practice of using molecular HIV epidemiology (MHE) to enhance surveillance activities has generated much discussion, partly because it typically involves sequencing viral samples from persons living with HIV without their knowledge or consent. Methods Using individual, semi-structured in-depth interviews, we asked 41 individuals from a range of groups affected and/or involved in MHE and related health services in North Carolina their views about consent and MHE. Findings Although there was no unanimity of opinion, our interview participants were largely (82.5%) supportive using MHE for public health surveillance without obtaining consent, including those living with HIV, though there was also broad support across groups for raising public awareness about MHE. The reasons against consent for MHE included: consent is not traditionally solicited or required in other medical or public health surveillance activities; consent for MHE could deter people from getting tested or entering care; refusals could diminish the accuracy and utility of MHE data due to the resulting evidence gaps; and consent is impractical when there is an urgent need for data during disease outbreaks. Reasons in favor of consent included: a sample is something personal for which it is appropriate to ask permission for its use; failure to ask for consent is an unjustified curtailment of personal rights; people should be able to choose what information related to themselves that they share or do not share with others. There were also mixed responses, where the appropriateness of asking for consent depended on certain conditions. Conclusion These study findings reveal some support among communities of interest for the current approach to consent along with a need for greater community awareness of MHE, and contribute to the ongoing policy conversation about whether the current practice of not obtaining consent for MHE and HIV surveillance purposes should be revisited.